2020
DOI: 10.1371/journal.ppat.1008518
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a fungal competition factor: Production of a conidial cell-wall associated antifungal peptide

Abstract: Competition is one of the fundamental driving forces of natural selection. Beauveria bassiana is a soil and plant phylloplane/root fungus capable of parasitizing insect hosts. Soil and plant environments are often enriched with other fungi against which B. bassiana competes for survival. Here, we report an antifungal peptide (BbAFP1), specifically expressed and localized to the conidial cell wall and is released into the surrounding microenvironment inhibiting growth of competing fungi. B. bassiana strains exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 78 publications
0
36
0
Order By: Relevance
“…These suggestions have been confirmed in experiments involving cell-free culture filtrates (Renwick, Campbell & Coe, 1991;Bark et al, 1996;Sasan & Bidochka, 2013;Lozano-Tovar et al, 2017). It was also shown that B. bassiana produces an antifungal peptide (BbAFP1) that inhibits the growth of Alternaria brassicae (Tong et al, 2020). The activity of Metarhizium extracts against Phytophthora sojae and Aphanomyces cochlioides was associated with the secondary metabolites aurovertins and fungerin, N-(methyl-3-oxodec-6-enoyl)-2-pyrroline, and N-(methyl-3-oxodecanoyl)-2-pyrroline (Putri et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…These suggestions have been confirmed in experiments involving cell-free culture filtrates (Renwick, Campbell & Coe, 1991;Bark et al, 1996;Sasan & Bidochka, 2013;Lozano-Tovar et al, 2017). It was also shown that B. bassiana produces an antifungal peptide (BbAFP1) that inhibits the growth of Alternaria brassicae (Tong et al, 2020). The activity of Metarhizium extracts against Phytophthora sojae and Aphanomyces cochlioides was associated with the secondary metabolites aurovertins and fungerin, N-(methyl-3-oxodec-6-enoyl)-2-pyrroline, and N-(methyl-3-oxodecanoyl)-2-pyrroline (Putri et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Altogether, these results suggest that mannoproteins determine AfpB interaction with the cell wall and, thus, its antifungal activity. (29,(31)(32)(33)(34). ROS production was monitored in these studies after long and high-concentration treatments, with deleterious effects observed; it was unclear whether ROS was signaling or a consequence of cell death.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of reactive oxygen species (ROS) is associated with cell death, acting either as signaling molecules in regulated cell death or as toxic compounds causing oxidative damage to lipids, proteins, and nucleic acids and uncontrolled cell destruction. Several studies have previously reported the production of ROS in fungal cells triggered by AFPs ( 29 , 31 34 ). ROS production was monitored in these studies after long and high-concentration treatments, with deleterious effects observed; it was unclear whether ROS was signaling or a consequence of cell death.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that entomopathogenic fungi produce various secondary metabolites and enzymes (oosporeins, destruxins, different proteinases, AMPs) for inhibiting both host immune responses and competitive microorganisms [ 36 , 48 , 49 ]. The set of enzymes and secondary metabolites present is significantly different between fungal species and depends on host and habitat specificity.…”
Section: Introductionmentioning
confidence: 99%